2010
DOI: 10.1055/s-0030-1250036
|View full text |Cite
|
Sign up to set email alerts
|

Pinoresinol-Lariciresinol Reductases with Opposite Enantiospecificity Determine the Enantiomeric Composition of Lignans in the Different Organs ofLinum usitatissimumL.

Abstract: Lignans in higher plants represent an ideal class of natural products to be investigated for the origin of stereochemical diversity since chiral lignans occur in pure enantiomeric form as well as in enantiomeric mixtures. Seeds of Linum usitatissimum contain 8S, 8'S-(+)- and 8R, 8'R-(-)-secoisolariciresinol [SS-(+)- and RR-(-)-secoisolariciresinol, respectively] as diglucosides (SS- and RR-secoisolariciresinol diglucosides) whereas aerial parts of flowering L. usitatissimum accumulate only lignans derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 26 publications
1
43
1
Order By: Relevance
“…Although promoter-GUS analyses and semiquantitative PCR indicated that the LuPLR1 gene cloned was not expressed in flax stem tissues (Hano et al, 2006b), the recent cloning of a second PLR gene (LuPLR2; Hemmati et al, 2010) from leaves and stems of flax plants, together with our results, suggest that PLR genes in flax form a small multigene family with organ-/tissuespecific expression patterns. Two other highly abundant neolignan unigene transcripts in flax inner stem tissues correspond to the enzyme PCBER, catalyzing the reduction of DDC into IDDDC and identified previously as the most abundant protein in poplar xylem (Gang et al, 1999;Vander Mijnsbrugge et al, 2000).…”
contrasting
confidence: 60%
“…Although promoter-GUS analyses and semiquantitative PCR indicated that the LuPLR1 gene cloned was not expressed in flax stem tissues (Hano et al, 2006b), the recent cloning of a second PLR gene (LuPLR2; Hemmati et al, 2010) from leaves and stems of flax plants, together with our results, suggest that PLR genes in flax form a small multigene family with organ-/tissuespecific expression patterns. Two other highly abundant neolignan unigene transcripts in flax inner stem tissues correspond to the enzyme PCBER, catalyzing the reduction of DDC into IDDDC and identified previously as the most abundant protein in poplar xylem (Gang et al, 1999;Vander Mijnsbrugge et al, 2000).…”
contrasting
confidence: 60%
“…(+)-Secoisolariciresinol is then glycosylated to secoisolariciresinol diglucoside (SDG) that accumulates to high levels in flax seeds (linseed; Ford et al, 2001). The complexity of lignan stereochemistry was underlined in a recent study (Hemmati et al, 2010) that isolated two PLRs (PLR-Lu1, PLR-Lu2) showing opposite enantiospecificity. PLR-Lu1 utilizes 8S,8′S-pinoresinol, whereas PLR-Lu2 uses 8R,8′R-pinoresinol.…”
Section: Dimerization Of Monolignols and Synthesis Of (Neo)lignansmentioning
confidence: 99%
“…PLR-Lu1 utilizes 8S,8′S-pinoresinol, whereas PLR-Lu2 uses 8R,8′R-pinoresinol. Interestingly, gene expression analyses have shown that the Lu PLR1 gene is expressed in different flax seed tissues, whereas the Lu PLR2 gene is expressed in flax stem and leaf tissues (Hano et al, 2006; Hemmati et al, 2010; Venglat et al, 2011). In agreement with this organ-specific gene expression, 8S,8′S-SDG accumulates in flax seeds whereas aerial green parts accumulate 8R,8′R-SDG.…”
Section: Dimerization Of Monolignols and Synthesis Of (Neo)lignansmentioning
confidence: 99%
“…LuPLR1 is responsible for the synthesis of the major (+)-secoisolariciresinol enantiomer (87%) while a minor quantity of the (–)-secoisolariciresinol enantiomer (13%) is synthesized by LuPLR2 (Hemmati et al, 2010). The very weak β-glucuronidase ( GUS ) activity detected in embryos has to be attributed to non-specific GUS that has already been reported in seeds of a number of plants (Hu et al, 1990; Hänsch et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…RNAi technology applied to down regulate LuPLR1 gene expression in flax ( Linum usitatissimum L.) seeds has evidenced the direct in vivo implication of the LuPLR1 gene in the biosynthesis of (+)-SDG (Renouard et al, 2014). LuPLR2 , another PLR gene, encoding a protein with an enantiospecificity opposite to LuPLR1 exists in flaxseeds (Hemmati et al, 2010). LuPLR2 is responsible for the synthesis of the minor (–)-secoisolariciresinol enantiomer.…”
Section: Introductionmentioning
confidence: 99%